2021
DOI: 10.1097/ju.0000000000001873
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenic Obesity and its Prognostic Impact on Urological Cancers: A Systematic Review

Abstract: Purpose: Sarcopenia, an age-related loss of muscle mass and function, may predict adverse outcomes for patients with urological cancers. However, the clinical implications and significance of sarcopenic obesity are not well understood. We systematically reviewed data on the prevalence and prognostic impact of sarcopenic obesity for patients with renal cell carcinoma, urothelial carcinoma and prostate cancer undergoing treatment. Materials and Methods: We searched EMBASEÒ, PubMedÒ/MEDLINEÒ and ScopusÒ for relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…Therefore, some scholars adjust the measurement of skeletal muscle from fat composition. Mintziras [ 34 , 35 ] believes that this sarcopenia obesity (SO) reflects a worse physical condition than sarcopenia. With the continuous increase of obesity rate, this adjustment may be more accurate and appropriate, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some scholars adjust the measurement of skeletal muscle from fat composition. Mintziras [ 34 , 35 ] believes that this sarcopenia obesity (SO) reflects a worse physical condition than sarcopenia. With the continuous increase of obesity rate, this adjustment may be more accurate and appropriate, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…However, low muscle mass is also an important component of malnutrition. Increasing number of studies have found that sarcopenic obesity is associated with a poor prognosis in patients 24–28 . Therefore, the assessment of muscle mass is of great value in identifying malnutrition in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing number of studies have found that sarcopenic obesity is associated with a poor prognosis in patients. [24][25][26][27][28] Therefore, the assessment of muscle mass is of great value in identifying malnutrition in obese patients. mALI, which integrates muscle mass, nutrition, and inflammation parameters, is a promising indicator for further assessment of malnutrition and prognosis in overweight or obese LC patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that muscle and adipose tissue both have endocrine function influencing the inflammatory and metabolic status of the body in somewhat of a yin and yang relationship 6 . Patients with prostate cancer who have high fat mass levels exhibit much poorer prognosis, including risk of mortality; 7 however, the evidence around high fat and low muscle ( sarcopenic obesity) is somewhat inconclusive at this stage and requires more high‐quality research 8 . Regardless, both obesity and sarcopenic obesity greatly increase risk of other chronic diseases such as cardiovascular and metabolic disorders and should be addressed as a priority for exercise prescription in these patients.…”
Section: High Fat Mass Is Problematicmentioning
confidence: 99%
“…6 Patients with prostate cancer who have high fat mass levels exhibit much poorer prognosis, including risk of mortality; 7 however, the evidence around high fat and low muscle (sarcopenic obesity) is somewhat inconclusive at this stage and requires more high-quality research. 8 Regardless, both obesity and sarcopenic obesity greatly increase risk of other chronic diseases such as cardiovascular and metabolic disorders and should be addressed as a priority for exercise prescription in these patients. Exercise alone is not very effective for inducing fat loss.…”
Section: High Fat Mass Is Problematicmentioning
confidence: 99%